2021
DOI: 10.1039/d0ew00893a
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration and characterization of five pathogenic Legionella species from large research and educational buildings

Abstract: This graph compares the potential amplification of Legionella spp. and specific pathogenic species in the premise plumbing of five buildings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…For example, the culture method takes up to 10 days for results, it is incapable of enumerating viable but non-culturable cells (VBNC), and it is unable to identify Legionella species in a precise manner [50]. However, quantitative assessment using PCR can provide critical results on bacterial and amoebae concentrations to determine if there is amplification at a particular exposure site [51,52]. Digital droplet PCR was very useful and can be used to assess duplex assays for various species, as described in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the culture method takes up to 10 days for results, it is incapable of enumerating viable but non-culturable cells (VBNC), and it is unable to identify Legionella species in a precise manner [50]. However, quantitative assessment using PCR can provide critical results on bacterial and amoebae concentrations to determine if there is amplification at a particular exposure site [51,52]. Digital droplet PCR was very useful and can be used to assess duplex assays for various species, as described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sample concentrations were transformed from (GC)/100 mL into Log 10 GC/100 mL. Biological data were expressed as geometric means, and chemical data were shown as arithmetic means with standard deviation [52]. Statistical results were interpreted at the level of significance p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Building plumbing characteristics have been shown to greatly influence tap water quality. Building plumbing properties, including high surface-to-volume ratios, periods of stagnation, and equilibration with building temperatures, create an environment that contributes to the growth of biofilms and high concentrations of certain opportunistic human pathogens (OPs), including NTM (12,13). Although previous studies have found that building plumbing may contribute to high concentrations of NTM, few studies have evaluated the impacts of flushing, seasonal variations, and water quality parameters (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%